2010
DOI: 10.1007/s13277-010-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pretreatment hematologic profile on survival of colorectal cancer patients

Abstract: Pretreatment hematologic abnormalities have been reported to have prognostic value in patients with solid tumors. The aim of our study was to determine the prevalence of abnormalities in the hematologic profile in patients with colorectal cancer before treatment and to evaluate if such a profile could be used for prognostic evaluations. We identified all patients in Cancer Center of Sun Yat-Sen University who were diagnosed as colorectal cancers between May 2005 and August 2009. All subjects were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 25 publications
4
46
0
2
Order By: Relevance
“…The most likely explanation for the association between low HB and poor DSS is the presence of macro‐hematuria in larger tumors. Increased levels of inflammatory cytokines, which might suppress the bone marrow, and other multifactorial molecular mechanisms could also be accountable for the association . The present study showed significant nutritional deficiency, as estimated by the albumin level and BMI in the low HB group (<10.5 g/dL).…”
Section: Discussionsupporting
confidence: 48%
“…The most likely explanation for the association between low HB and poor DSS is the presence of macro‐hematuria in larger tumors. Increased levels of inflammatory cytokines, which might suppress the bone marrow, and other multifactorial molecular mechanisms could also be accountable for the association . The present study showed significant nutritional deficiency, as estimated by the albumin level and BMI in the low HB group (<10.5 g/dL).…”
Section: Discussionsupporting
confidence: 48%
“…We have previously [23] shown that the percentages of leukocytosis, anemia, and thrombocytosis were significantly higher in colorectal cancer patients than in patients with benign diseases. Moreover, we found that both pretreatment anemia and thrombocytosis were independent prognostic variables for survival of colorectal cancer patients.…”
Section: Introductionmentioning
confidence: 89%
“…A similar phenomenon was found in the condition of anemia and leukocytosis. The incidence rates of anemia and leukocytosis in patients with solid tumors were in a range of 9% to 42.6% [7,22] and 7.4% to 39.0% [7,22,23], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the 70–79 years age group, leukocytosis was an independent prognostic factor. There was some evidence that leukocytosis is an independent prognostic factor in solid tumors such as cervical cancer, colon cancer and lung cancer [23,24,25]. Trivanovic et al [26] also showed that leukocytosis is a poor prognostic factor using univarinate, but not mutivarinate, Cox regression.…”
Section: Discussionmentioning
confidence: 99%